Do you know this syndrome? - Pedro Vale Machado; Egon Luiz Rodrigues Daxbacher; Daniel Lago Obadia; Edna Ferreira da Cunha; Maria de Fátima Guimarães Scotelaro Alves; Danielle Mann (Sociedade Brasileira de Dermatologia, 2013)
Berardinelli-Seip syndrome is a rare autosomal recessive disease characterized by inadequate metabolism and inefficient storing of lipids in fat cells, generating accumulation of fat in organs such as the liver, spleen, pancreas, heart, arterial endothelium and skin. Classically, patients manifest generalized lipoatrophy at birth or until 2 years of age, and in adolescence usually develop marked insulin resistance with rapid progression to diabetes and dyslipidemia. We report the case of a 17-year-old Berardinelli-Seip syndrome patient with eruptive xanthoma associated with severe hypertriglyceridemia. It is worth noting Eruptive xanthoma as a dermatological manifestation that is not generally highlighted in the reports of cases of this genetic metabolic disorder.